Hepatotoxicity and renal toxicity induced by radiation and the protective effect of quercetin in male albino rats. (2nd September 2022) - Baran, Munevver; Yay, Arzu; Onder, Gozde Ozge; canturk Tan, Fazile; Yalcin, Betul; Balcioglu, Esra; Yıldız, Oguz Galip
Abstract: Purpose: Although radiation is one of the basic methods commonly used in cancer treatment, it inevitably enters the field of treatment in healthy tissues and is adversely affected by the acute and chronic side effects of radiation. This study evaluated the possible protective effects of quercetin, an antioxidant agent, against liver and kidney damage in rats exposed to a whole-body single dose of radiation (10 Gy of gamma-ray). Materials and methods: The study groups were formed as control, sham, quercetin, radiation, quercetin + radiation and radiation + quercetin using 60 male Wistar albino (200–250 g, 3 months old) rats, including 10 rats in each group. The gamma-ray provided by the Co60 teletherapy machine was given to the whole body as external irradiation. According to the groups, quercetin was administered to rats at 50 mg/kg/day via oral gavage before or after radiation administration. The rats were sacrificed the day after irradiation and the extracted tissue samples from all groups were compared histologically and immunohistochemically. DNA damage was determined by the neutral comet assay technique. Also, malondialdehyde (MDA) and glutathione peroxidase (GSH) were evaluated in liver and kidney tissues by the ELISA method. Results: Histopathological changes were observed altered morphology of liver and kidney tissues in the radiation groups. Sinusoidal dilatations, vacuolization, and hepatic parenchyma necrosis in the liver, while in kidneys, glomerular shrinkage, widened Bowman's space, tubular dilatation, and inflammation were evident. TNF-α, IL1-α, HIF1-α, and caspase 3 immunoreactivities in tissues were determined by immunohistochemistry. High caspase 3 positive cell number confirmed apoptosis, the comet parameters were decreased in the quercetin + radiation group. When compared to the control group, the exposure to radiation showed a marked elevation in MDA which was accompanied by high GSH. This damage was reduced in the quercetin + radiation group. Conclusions: With the results obtained from the study; Quercetin is thought to have a protective potential against radiation-induced liver and kidney damage due to its radioprotective effect.